2021
DOI: 10.1182/blood.2020010456
|View full text |Cite
|
Sign up to set email alerts
|

“Mast”ering drug discovery with iPSCs

Abstract: In this issue of Blood, Toledo et al describe the generation of KIT D186Vinduced pluripotent stem cells (iPSCs) from patients with aggressive systemic mastocytosis (SM) to use as patient-specific models for mechanistic studies and drug discovery. Using these iPSCs, the authors identified nintedanib, a US Food and Drug Administration-approved angiokinase inhibitor, as a potential new therapy for SM. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Because of this, the presence of mutations in limited sets of genes has been included in several recently proposed risk stratification models for both AdvSM (i.e., SRSF2/ASXL1/RUNX1 [11], SRSF2/ASXL1/RUNX1/EZH2 [13], ASXL1/RUNX1/NRAS [120]) and Non-AdvSM (e.g., ASXL1/RUNX1/DNMT3A [12]). The recent development of SM-induced pluripotent stem cells (iPSCs) positive for KIT D816V and other concurrent mutations [180], which accurately reflect the genetic background of SM patients' multi-mutated pathological cells, may become a powerful tool to dissect the impact of these mutations on the aetiopathogenic mechanisms involved in disease progression [181]. Therefore, molecular characterization of the genetic background of AdvSM patients, including NGS as described above, VAF assessment of somatic mutations [125,182] and drug screening in patient-derived iPSCs [180,183], may lead to improved molecularly targeted treatment options in a context of personalized precision medicine.…”
Section: Prognostic Impact Of Acquired Gene Mutations In Systemic Mas...mentioning
confidence: 99%
“…Because of this, the presence of mutations in limited sets of genes has been included in several recently proposed risk stratification models for both AdvSM (i.e., SRSF2/ASXL1/RUNX1 [11], SRSF2/ASXL1/RUNX1/EZH2 [13], ASXL1/RUNX1/NRAS [120]) and Non-AdvSM (e.g., ASXL1/RUNX1/DNMT3A [12]). The recent development of SM-induced pluripotent stem cells (iPSCs) positive for KIT D816V and other concurrent mutations [180], which accurately reflect the genetic background of SM patients' multi-mutated pathological cells, may become a powerful tool to dissect the impact of these mutations on the aetiopathogenic mechanisms involved in disease progression [181]. Therefore, molecular characterization of the genetic background of AdvSM patients, including NGS as described above, VAF assessment of somatic mutations [125,182] and drug screening in patient-derived iPSCs [180,183], may lead to improved molecularly targeted treatment options in a context of personalized precision medicine.…”
Section: Prognostic Impact Of Acquired Gene Mutations In Systemic Mas...mentioning
confidence: 99%
“…To overcome this limitation, Toledo et al generated the induced pluripotent stem cells (iPSCs) from patients with aggressive SM, which represents a new approach for disease modeling and screening for precision medicine. Using these iPSCs, the authors identified nintedanib, which is a FDA approved angiokinase inhibitor that targets the vascular endothelial growth factor receptor (EGFR) and fibroblast growth factor receptor, as a novel KIT D816V inhibitor [102,103]. Table 5 summarizes the main recruiting clinical trials in SM.…”
Section: Future Perspectivesmentioning
confidence: 99%